A bifunctional material and a method for enhancing methane catalytic oxidation by adsorption

CN120515253BActive Publication Date: 2026-11-03TIANJIN UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510625968.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2026-11-03
Estimated Expiration
2045-05-15

AI Technical Summary

Technical Problem

While existing catalytic oxidation technologies offer advantages such as low reaction temperature and low energy consumption when treating low concentrations of methane, they fail to effectively control and utilize the reaction product CO2, leading to new emission burdens in greenhouse gas control.

Method used

A bifunctional material is used to combine catalytically active components and CO2 adsorption components to prepare a catalyst through mechanical mixing, achieving simultaneous separation of low-concentration methane catalytic oxidation and product CO2. The adsorbed CO2 is treated by high-temperature calcination or hydrogen atmosphere regeneration.

Benefits of technology

The efficient catalytic oxidation of low-concentration methane and in-situ separation of CO2 were achieved under mesophilic conditions, reducing the CO2 concentration in the exhaust gas, improving the efficiency of synergistic greenhouse gas emission reduction, and providing a resource utilization pathway for CO2. The material exhibits good structural stability and economic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120515253B_ABST
    Figure CN120515253B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of methane catalytic oxidation, and discloses a kind of bifunctional material, and based on the material, a kind of new adsorption enhanced methane catalytic oxidation method is constructed.The bifunctional material is mixed by methane catalytic oxidation catalyst and calcium-based CO2 adsorbent, and has the ability to realize methane catalytic oxidation and in-situ capture of product CO2 simultaneously under medium temperature conditions, which can effectively promote the forward movement of the reaction, improve the methane conversion efficiency and reduce CO2 emissions;The process sets high temperature calcination and hydrogen atmosphere two regeneration modes, respectively realizes CO2 desorption or reduction conversion into CO and other small molecule carbon-containing products, and takes into account the CO2 capture and resource utilization goals.The application has the advantages of strong material thermal stability, excellent cycle performance, significant emission reduction effect, etc., and is suitable for greenhouse gas co-management and resource utilization of low-concentration methane gas such as coal mine ventilation air methane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of methane catalytic oxidation technology. Specifically, it relates to a bifunctional material and its preparation method, and an adsorption-enhanced methane catalytic oxidation process based on the bifunctional material. Background Technology

[0002] Methane, the second largest greenhouse gas after CO2, has a much higher global warming potential than CO2 and has received widespread attention in global climate governance. Since the COP26 meeting, methane emission reduction has been incorporated into the core content of the international climate agenda. During coal production, a large amount of low-concentration methane is emitted through mine exhaust gas, accounting for more than 93% of methane emissions from coal production. Due to its low concentration and wide distribution, traditional recycling methods are difficult, constituting a significant pollution source that urgently needs to be addressed.

[0003] Currently, technologies for treating low-concentration methane mainly focus on thermal oxidation and catalytic oxidation pathways. Among these, catalytic oxidation technology has received widespread attention in academic research and engineering applications due to its advantages such as low reaction temperature, relatively low energy consumption, and less secondary pollution. However, existing catalytic oxidation methods primarily focus on the efficient conversion of methane, while paying insufficient attention to the control and resource utilization of CO2 in the reaction products. Since the catalytic oxidation of methane inevitably produces a large amount of CO2, if it is not effectively captured and utilized, it will create a new emission burden in greenhouse gas control. Summary of the Invention

[0004] The main objective of this invention is to provide a bifunctional material capable of simultaneously achieving the catalytic oxidation of low-concentration methane and the capture of the product CO2, while also establishing a novel adsorption-enhanced method for the catalytic oxidation of methane. This invention breaks through the traditional research framework limited to the catalytic oxidation of methane, and for the first time systematically constructs a bifunctional material possessing both mesophilic catalytic activity and CO2 adsorption capacity. It achieves in-situ capture of the product CO2 while catalytically oxidizing methane, effectively reducing CO2 emissions and possessing the potential for resource utilization. This provides a novel technical pathway that balances economic and environmental benefits for the resource utilization of coal mine gas and the synergistic reduction of greenhouse gas emissions.

[0005] To achieve the above-mentioned objectives, the present invention is implemented through the following technical solution:

[0006] According to one aspect of the present invention, a bifunctional material is provided, comprising a mixture of a catalytically active component and a CO2 adsorption component, wherein the catalytically active component is a methane catalytic oxidation catalyst and the CO2 adsorption component is a calcium-based CO2 adsorbent; the bifunctional material is used to achieve a synergistic process of simultaneous separation of low-concentration methane catalytic oxidation and product CO2.

[0007] Furthermore, the mass ratio of the catalytically active component to the CO2 adsorption component is no greater than 1:7.

[0008] Furthermore, among them:

[0009] The methane catalytic oxidation catalyst is selected from one or more combinations of A, B, and C:

[0010] A is a single metal oxide composed of any non-noble metal element among Co, Ni, Cu, and Fe;

[0011] B is a doped oxide or composite oxide formed based on at least one non-noble metal element among Co, Ni, Cu, and Fe;

[0012] C is a supported catalyst in which either oxide of A or B is used as the active component and supported on the surface of the support.

[0013] The calcium-based CO2 adsorbent is CaO, CaO-based porous materials, calcined dolomite, or calcined calcite.

[0014] Furthermore, the calcination temperature of dolomite or calcite is 900-1000℃, and the calcination time is 3-4 hours.

[0015] Furthermore, the catalytically active component and the CO2 adsorption component are prepared by mechanical mixing; using any one of the following methods (1), (2), and (3):

[0016] Method (1): The catalytically active component and the CO2 adsorption component are mixed and then compressed into tablets;

[0017] Method (2): The catalytic active component and the CO2 adsorption component are compressed into tablets and then mixed uniformly;

[0018] Method (3): The catalytic active component and the CO2 adsorption component are compressed into tablets and then mixed with the catalytic active component on top and the CO2 adsorption component on the bottom.

[0019] According to another aspect of the present invention, an adsorption-enhanced methane catalytic oxidation method using the above-mentioned bifunctional material is provided, comprising a catalytic oxidation stage and a regeneration stage;

[0020] The reaction gas in the catalytic oxidation stage is a mixture of low-concentration methane, oxygen, and nitrogen.

[0021] The bifunctional material in the catalytic oxidation stage adsorbs CO2 in the product while catalytically oxidizing methane, thus promoting the methane oxidation reaction and achieving simultaneous CO2 separation.

[0022] The regeneration stage releases or converts the CO2 adsorbed by the bifunctional material, thereby regenerating the bifunctional material.

[0023] Furthermore, in the reaction gas of the catalytic oxidation stage: the volume fraction of low-concentration methane is 0.5%-5%, the volume fraction of oxygen is less than 21%, and the remainder is nitrogen.

[0024] Furthermore, the reaction conditions for the catalytic oxidation stage are 450-650℃.

[0025] Furthermore, the regeneration stage includes high-temperature calcination regeneration and hydrogen atmosphere regeneration.

[0026] The high-temperature calcination regeneration method involves calcining the bifunctional material to release the adsorbed CO2.

[0027] The hydrogen atmosphere regeneration method involves introducing H2 under isothermal conditions during the catalytic oxidation stage to convert the adsorbed CO2 into small molecule carbon-containing reduction products such as CO.

[0028] Furthermore, the calcination temperature of the high-temperature calcination regeneration method is 900-1000℃.

[0029] Preferred,

[0030] The beneficial effects of this invention are:

[0031] (I) This invention prepares a bifunctional material by combining a methane catalytic oxidation catalyst with a calcium-based CO2 adsorbent. This material can simultaneously achieve efficient catalytic oxidation of low-concentration methane and in-situ separation of CO2 products in a single reaction system, significantly reducing the CO2 concentration in the tail gas and improving the overall greenhouse gas emission reduction efficiency.

[0032] (ii) The bifunctional material of the present invention exhibits good catalytic activity and CO2 adsorption capacity under medium temperature conditions. Compared with traditional catalysts that only have catalytic function, the bifunctional material can promote the forward movement of the reaction by introducing CO2 adsorbent, improve the methane conversion rate within the same temperature range, and reduce CO2 emissions, thus having better environmental benefits and reaction performance.

[0033] (III) The adsorption-enhanced methane catalytic oxidation method based on bifunctional materials of the present invention, such as Figure 1 As shown, two material regeneration methods suitable for different working conditions are provided. In the high-temperature calcination regeneration mode, adsorbed CO2 can be released to obtain pure CO2, which is suitable for scenarios such as carbon capture and storage (CCS). In the hydrogen atmosphere regeneration mode, CO2 can be converted and utilized as a resource, such as small molecule carbon-containing reduction products such as syngas (CO) and CH4, thus broadening the downstream application path.

[0034] (iv) The bifunctional material of the present invention is prepared by mechanical mixing process. The material has a stable structure, uniform component distribution, good recyclability and thermal stability, and is suitable for long-term operation under industrial conditions.

[0035] (v) The non-precious metal oxide catalyst and calcium-based CO2 adsorbent used in the bifunctional material of the present invention are widely available, inexpensive, and easy to prepare, and have good economic and industrialization potential. Attached Figure Description

[0036] Figure 1 This is a schematic diagram of the reaction of the bifunctional material of the present invention used in the adsorption-enhanced methane catalytic oxidation method.

[0037] Figure 2 The results are the cycle stability test results of the 10CoCe / BYS catalytic oxidation stage under the conditions of Example 14.

[0038] Figure 3 The results are the cycle stability test results of the 10CoCe / BYS regeneration stage under the conditions of Example 14.

[0039] Figure 4 These are XRD patterns of the fresh bifunctional materials prepared in Examples 1-3.

[0040] Figure 5 The XRD characterization of the 10CoCe / BYS bifunctional material under the conditions of Examples 1, 9, and 14 is shown. Detailed Implementation

[0041] The present invention will be further described in detail below through specific embodiments. These embodiments will enable those skilled in the art to have a more comprehensive understanding of the present invention, but will not limit the present invention in any way.

[0042] This invention uses a CoCe bimetallic oxide catalyst as an example for illustration. Those skilled in the art will understand that other non-noble metal oxide catalysts, such as single or bimetallic oxides of elements like Co, Ni, Cu, and Fe, as well as their doped, solid-solution, composite oxide, or supported structures, can be mechanically mixed with calcium-based CO2 adsorbents to form bifunctional materials, which can then be used in the adsorption-enhanced methane catalytic oxidation process of this invention. Those skilled in the art can achieve similar synergistic catalytic / adsorption effects by substituting materials and optimizing structures without departing from the core concept of this invention, and all such substitutions should be considered within the scope of protection of this invention.

[0043] Example 1

[0044] A CoCe bimetallic oxide catalyst with a Co3O4 mass fraction of 10% was prepared by co-precipitation and named 10CoCe. Natural dolomite was selected as the precursor and calcined at 900℃ for 3 hours in air. After calcination, it was cooled to room temperature and ground into powder to serve as a calcium-based CO2 adsorbent. The obtained 10CoCe powder and the calcium-based CO2 adsorbent powder were mixed at a mass ratio of 1:7 and ground for 10 minutes to ensure thorough mixing. The mixed sample powder was then pressed into tablets (8 MPa) and sieved (20-40 mesh) to obtain granular bifunctional material, named 10CoCe / BYS.

[0045] Example 2

[0046] The bifunctional material was prepared according to the method of Example 1, except that the calcium-based CO2 adsorbent precursor was selected from natural calcite. The bifunctional material was named 10CoCe / FJS.

[0047] Example 3

[0048] The bifunctional material was prepared according to the method of Example 1, except that the calcium-based CO2 adsorbent used was commercial CaO (without calcination), and the resulting sample was named 10CoCe / CaO.

[0049] Example 4

[0050] The bifunctional material was prepared according to the method of Example 3, except that the mass ratio of 10CoCe powder to calcium-based CO2 adsorbent powder during mixing was 1:0, that is, the bifunctional material contained only 10CoCe.

[0051] Example 5

[0052] The bifunctional material was prepared according to the method of Example 3, except that the mass ratio of 10CoCe powder to calcium-based CO2 adsorbent powder was 2:1 during mixing.

[0053] Example 6

[0054] The bifunctional material was prepared according to the method of Example 3, except that the mass ratio of 10CoCe powder to calcium-based CO2 adsorbent powder was 1:1 during mixing.

[0055] Example 7

[0056] The bifunctional material was prepared according to the method of Example 1, except that the mixing method was as follows: 10CoCe powder and calcium-based CO2 adsorbent were pressed into tablets and then mixed uniformly according to the mass ratio.

[0057] Example 8

[0058] The bifunctional material was prepared according to the method of Example 1, except that the mixing method was as follows: 10CoCe powder and calcium-based CO2 adsorbent were compressed into tablets and then mixed in a mass ratio with 10CoCe on top and calcium-based CO2 adsorbent on the bottom.

[0059] Example 9

[0060] 0.8 g of the prepared bifunctional material from Example 1 was mixed with an equal volume of quartz sand and then placed into a fixed-bed quartz reaction tube for testing. The reactor was heated at a constant rate of 10 °C / min, and the reaction was initiated at 600 °C under a N2 atmosphere (50 ml / min). During the catalytic oxidation stage, a 1% CH4 / 20% O2 / N2 mixed gas (50 ml / min) was introduced for 5 min. Subsequently, a high-temperature calcination regeneration mode was used, switching the gas to N2 (50 ml / min) and raising the temperature to 900 °C for 10 min. After the reaction was completed, the temperature was lowered to 600 °C to repeat the catalytic oxidation stage, and this cycle was repeated continuously.

[0061] Example 10

[0062] The performance test was performed according to the steps of Example 9, with the only difference being that the temperature of the catalytic oxidation stage was 450°C.

[0063] Example 11

[0064] The performance test was performed according to the steps of Example 9, with the only difference being that the temperature of the catalytic oxidation stage was 500°C.

[0065] Example 12

[0066] The performance test was performed according to the steps of Example 9, with the only difference being that the temperature during the catalytic oxidation stage was 550°C.

[0067] Example 13

[0068] The performance test was performed according to the steps of Example 9, with the only difference being that the temperature during the catalytic oxidation stage was 575°C.

[0069] Example 14

[0070] The performance test was performed according to the steps of Example 9, with the only difference being that the temperature during the catalytic oxidation stage was 625°C.

[0071] Example 15

[0072] The performance test was performed according to the steps of Example 9, with the only difference being that the temperature during the catalytic oxidation stage was 650°C.

[0073] Example 16

[0074] The performance test was carried out according to the steps of Example 9, the only difference being that the regeneration stage adopted a hydrogen atmosphere regeneration mode, and the reaction was carried out under isothermal conditions in the catalytic oxidation stage with 20% H2 / N2 gas (50 ml / min) for 10 minutes. The catalytic oxidation stage and the regeneration stage need to be purged with N2 (50 ml / min).

[0075] To evaluate the reactivity of the bifunctional materials of this invention, the bifunctional materials prepared in Examples 1-7 were tested and evaluated using an evaluation device. The test conditions were as shown in Example 9. The tail gas composition was analyzed by chromatography, and the CH4 conversion rate and CO2 concentration in the catalytic oxidation stage were calculated. All test data were performance data after 1 minute of reaction.

[0076] The calculation method for CH4 conversion rate is as follows:

[0077]

[0078] The method for calculating CO2 concentration is as follows:

[0079]

[0080] in The values ​​represent the molar flow rates (mol / min) of CO2, CH4, O2, and N2, respectively, and the gas concentrations in the products are all volume concentrations. The results are shown in Table 1-3.

[0081] Table 1: Performance data of bifunctional materials with different synthesis parameters in the adsorption-enhanced catalytic oxidation of methane (reaction temperature 600℃)

[0082] <![CDATA[CH4 conversion rate (%)]]> <![CDATA[CO₂ concentration (%)]]> Example 1 100.0 0.008 Example 2 99.9 0.301 Example 3 99.6 0.367 Example 4 86.3 0.249

[0083] Table 2: Performance data of 10CoCe / BYS with different mechanical mixing methods in the adsorption-enhanced catalytic oxidation of methane (reaction temperature: 600℃, test data are performance data from the first cycle).

[0084] <![CDATA[CH4 Conversion Rate (%)]]> <![CDATA[CO₂ Concentration (%)]]> Example 1 100 0.201 Example 7 100 0.068 Example 8 100 0.325

[0085] Table 3: Performance data of 10CoCe / CaO with different mass ratios in the adsorption-enhanced catalytic oxidation of methane (reaction temperature 650℃)

[0086] <![CDATA[CH4 Conversion Rate (%)]]> <![CDATA[CO₂ concentration (%)]]> Example 3 100.0 0.059 Example 5 100.0 0.256 Example 6 100.0 0.220

[0087] Examples 1-4 investigated the effects of combining different calcium-based CO2 adsorbents on the performance of the bifunctional material in the adsorption-enhanced methane catalytic oxidation process. As shown in Table 1, the methane conversion rate of all three bifunctional materials was significantly improved after introducing calcium-based CO2 adsorbents compared to 10CoCe alone. The methane conversion rate at 600℃ reached over 99.5%, an increase of 13% compared to 10CoCe. The CO2 adsorption performance of the bifunctional materials combined with different calcium-based CO2 adsorbents varied, with 10CoCe / BYS showing the best CO2 adsorption effect, resulting in a near-zero CO2 concentration in the product.

[0088] Examples 1 and 7-8 investigated the effects of different mixing methods on the performance of the bifunctional materials, as shown in Table 2. The methane conversion rate of the 10CoCe / BYS bifunctional materials prepared by all three methods reached 100% during the reaction, and all could adsorb CO2 from the products. Among them, the bifunctional material prepared by the mixing method in Example 7 had the strongest CO2 adsorption capacity, with a product CO2 concentration of only 0.068% in the first cycle reaction.

[0089] Examples 3 and 5-6 investigated the effect of different mass ratios on the performance of the bifunctional materials, as shown in Table 3. All three 10CoCe / CaO bifunctional materials with different ratios achieved 100% conversion in the methane conversion process, and the CO2 concentration in the product decreased with increasing CaO ratio. When the 10CoCe:CaO ratio was 1:7, the CO2 concentration in the product decreased to below 0.1%, specifically 0.059%. This confirms that the performance of the calcium-based CO2 adsorbent at this ratio basically meets the requirements; therefore, it is recommended that the mass ratio of 10CoCe:calcium-based CO2 adsorbent should not exceed 1:7.

[0090] To evaluate the reactivity of the bifunctional material of this invention, an evaluation device was used to test and evaluate the performance of the bifunctional material prepared in Example 1. The test conditions are as shown in Examples 9-14. The tail gas composition was analyzed by chromatography, and the CH4 conversion rate and CO2 concentration in the catalytic oxidation stage were calculated. All test data are performance data after 1 min of reaction.

[0091] The calculation method for CH4 conversion rate is as follows:

[0092]

[0093] The method for calculating CO2 concentration is as follows:

[0094]

[0095] The performance evaluation indicators for the regeneration stage include CO concentration, CH4 concentration, and CO2 concentration, calculated using the following formulas:

[0096]

[0097] Where F CO , The values ​​represent the molar flow rates (mol / min) of CO, CO2, CH4, O2, N2, and H2, respectively. All gas concentrations in the products are volume concentrations. The results are shown in Table 4-6.

[0098] Table 4: Performance data of 10CoCe / BYS in the adsorption-enhanced catalytic oxidation of methane at different reaction temperatures

[0099] <![CDATA[CH4 Conversion Rate (%)]]> <![CDATA[CO₂ Concentration (%)]]> Example 9 100.0 0.008 Example 10 72.9 0.007 Example 11 88.5 0.012 Example 12 95.9 0.119 Example 13 98.7 0.215 Example 14 100 0.006 Example 15 100 0.002

[0100] Table 5: Performance data of 10CoCe / BYS in the adsorption-enhanced catalytic oxidation of methane under different regeneration modes (regeneration stage)

[0101]

[0102] Table 6: Performance data of 10CoCe / BYS in the adsorption-enhanced catalytic oxidation of methane under different regeneration modes (catalytic oxidation stage after regeneration, reaction temperature 600℃)

[0103] <![CDATA[CH4 conversion rate (%)]]> <![CDATA[CO₂ concentration (%)]]> Example 9 100.0 0.005 Example 16 95.9 0

[0104] Examples 9-15 investigated the performance data of 10CoCe / BYS in the adsorption-enhanced catalytic oxidation of methane at different reaction temperatures, as shown in Table 4. At a reaction temperature of 600℃, the methane conversion rate reached 100%, and CO2 in the product was almost completely absorbed, indicating optimal reaction performance. Below 600℃, the methane conversion rate decreased, but the performance requirements were still largely met. Above 600℃, 10CoCe / BYS also exhibited excellent catalytic activity and CO2 adsorption capacity, meeting the performance requirements; however, higher temperatures led to greater energy loss and material sintering issues.

[0105] Examples 9 and 16 investigated the performance data of 10CoCe / BYS in the adsorption-enhanced catalytic oxidation of methane under different regeneration modes, as shown in Tables 5 and 6. Table 5 shows the performance data of the two modes in the regeneration stage. In the hydrogen atmosphere regeneration mode, the CO2 adsorbed in the catalytic oxidation stage is converted into CO, accompanied by a small amount of CH4 byproducts and some unconverted CO2, with a CO concentration of 0.437%. At this time, the main reactions are RWGS reaction and some methanation side reactions. In the high-temperature calcination regeneration mode, the CO2 adsorbed in the catalytic oxidation stage is released through high-temperature calcination. Table 6 shows the catalytic oxidation stage after regeneration. The CH4 conversion rate of the 10CoCe / BYS bifunctional material under both regeneration conditions can reach 100%, and the CO2 concentration is less than 0.01%, indicating that both modes can achieve a synergistic process of simultaneous separation of methane catalytic oxidation and product CO2.

[0106] In this invention, the cyclic stability of 10CoCe / BYS under the conditions of Example 16 was tested. (See attached...) Figure 2 Throughout the cycle, the methane conversion rate remained close to 100%, with an average conversion rate of 99.9%. This indicates that the bifunctional material exhibits relatively stable catalytic activity without significant performance degradation. Furthermore, the CO2 adsorption performance also demonstrated good stability. (Appendix) Figure 3 Cyclic stability testing was conducted on the 10CoCe / BYS bifunctional material during the regeneration phase. Over ten consecutive cycles, the CO concentration in the product remained consistently stable at around 0.4%, while the methane concentration remained at a low level, averaging 0.017% over the ten cycles. This demonstrates the excellent performance stability of the 10CoCe / BYS bifunctional material.

[0107] Appendix Figure 4 The XRD patterns of the fresh bifunctional materials prepared in Examples 1-3 show that all samples exhibited obvious diffraction peaks of CeO2. However, no characteristic diffraction peaks of Co3O4 were observed in the XRD pattern of the 10CoCe sample, indicating that Co species have entered the CeO2 lattice and formed a stable solid solution structure. This suggests that the original crystal structure of the catalyst was not destroyed during mechanical mixing. Furthermore, the XRD patterns show that CaO is present in all three bifunctional materials—10CoCe / BYS, 10CoCe / FJS, and 10CoCe / CaO—confirming the presence of CaO as a calcium-based CO2 adsorbent.

[0108] Appendix Figure 5XRD characterization of the 10CoCe / BYS bifunctional materials from Examples 1, 9, and 16, namely fresh samples, high-temperature calcination regeneration (900℃), and 0CoCe / BYS regenerated under a hydrogen atmosphere. All bifunctional material samples maintained the same main crystal phase structure, indicating that their crystal structure did not change significantly after oxidation-adsorption reactions and different regeneration stages, demonstrating the good structural stability of the bifunctional materials.

[0109] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many specific modifications under the guidance of the present invention without departing from the spirit and scope of the claims, and these modifications all fall within the scope of protection of the present invention.

Claims

1. A method for adsorption-enhanced catalytic oxidation of methane based on bifunctional materials, characterized in that, It includes a catalytic oxidation stage and a regeneration stage; The bifunctional material is composed of a mixture of a catalytically active component and a CO2 adsorption component. The catalytically active component is a methane catalytic oxidation catalyst, and the CO2 adsorption component is a calcium-based CO2 adsorbent. The bifunctional material is used to achieve a synergistic process of simultaneous separation of low-concentration methane catalytic oxidation and product CO2. The methane catalytic oxidation catalyst is selected from one or more combinations of A, B, and C: A is a single metal oxide composed of any non-noble metal element among Co, Ni, Cu, and Fe; B is a doped oxide or composite oxide formed based on at least one non-noble metal element among Co, Ni, Cu, and Fe; C is a supported catalyst in which either oxide of A or B is used as the active component and supported on the surface of the support. The calcium-based CO2 adsorbent is CaO, CaO-based porous material, calcined dolomite, or calcined calcite. The reaction gas in the catalytic oxidation stage is a mixture of low-concentration methane, oxygen, and nitrogen; the reaction conditions in the catalytic oxidation stage are 450-650 °C. The bifunctional material in the catalytic oxidation stage adsorbs CO2 in the product while catalytically oxidizing methane, thus promoting the methane oxidation reaction and achieving simultaneous CO2 separation. The regeneration stage releases or converts the CO2 adsorbed by the bifunctional material, thereby regenerating the bifunctional material; the regeneration stage includes high-temperature calcination regeneration and hydrogen atmosphere regeneration. The high-temperature calcination regeneration method involves calcining the bifunctional material to release the adsorbed CO2. The hydrogen atmosphere regeneration method involves introducing H2 under isothermal conditions during the catalytic oxidation stage to convert the adsorbed CO2 into small-molecule carbon-containing reduction products of CO.

2. The adsorption-enhanced methane catalytic oxidation method based on bifunctional materials according to claim 1, characterized in that, The mass ratio of the catalytically active component to the CO2 adsorption component is no greater than 1:

7.

3. The adsorption-enhanced methane catalytic oxidation method based on bifunctional materials according to claim 1, characterized in that, The calcination temperature of dolomite or calcite is 900-1000 ℃, and the calcination time is 3-4 h.

4. The adsorption-enhanced methane catalytic oxidation method based on bifunctional materials according to claim 1, characterized in that, The catalytically active component and the CO2 adsorption component are prepared by mechanical mixing. Use any one of the following methods (1), (2), or (3): Method (1): The catalytically active component and the CO2 adsorption component are mixed and then compressed into tablets; Method (2): The catalytic active component and the CO2 adsorption component are compressed into tablets and then mixed uniformly; Method (3): The catalytic active component and the CO2 adsorption component are compressed into tablets and then mixed with the catalytic active component on top and the CO2 adsorption component on the bottom.

5. The adsorption-enhanced methane catalytic oxidation method based on bifunctional materials according to claim 1, characterized in that, In the reaction gases of the catalytic oxidation stage, the volume fraction of low-concentration methane is 0.5%-5%, the volume fraction of oxygen is less than 21%, and the remainder is nitrogen.

6. The adsorption-enhanced methane catalytic oxidation method based on bifunctional materials according to claim 1, characterized in that, The calcination temperature of the high-temperature calcination regeneration method is 900-1000 °C.

Citation Information

Patent Citations

  • Carbon dioxide adsorption and methanation integrated bifunctional catalyst and preparation method thereof

    CN115608366A

  • Bifunctional catalyst for coupling CO2 capture and conversion as well as preparation method and application of bifunctional catalyst

    CN117772190A